QUIDDICH: QUick IDentification of DIagnostic CHaracters. (31st October 2019) - Kühn, A. Luise; Haase, Martin
Abstract: With the advent of molecular genetic methods, an increasing number of morphologically cryptic taxa has been discovered. The majority of them, however, remains formally undescribed and without a proper name although their importance in ecology and evolution is increasingly being acknowledged. Despite suggestions to complement traditional descriptions with genetic characters, the taxonomic community appears to be reluctant to adopt this proposition. As an incentive, we introduce QUIDDICH, a tool for the QUick IDentification of DIgnostic CHaracters, which automatically scans a DNA or amino acid alignment for those columns that allow to distinguish taxa and classifies them into four different types of diagnostic characters. QUIDDICH is a system‐independent, fast and user‐friendly tool that requires few manual steps and provides a comprehensive output, which can be included in formal taxonomic descriptions. Thus, cryptic taxa do not have to remain in taxonomic crypsis and, bearing a proper name, can readily be included in biodiversity assessments and ecological and evolutionary analyses. QUIDDICH can be obtained from the comprehensive R archive network (CRAN, https://cran.r-project.org/package=quiddich ). Abstract : To facilitate the incorporation of genetic characters into taxonomic descriptions, in particular of morphologically cryptic taxa, we developed QUIDDICH, an R package for the QUick IDentification of DIgnostic CHaracters. QUIDDICH identifies and tabs those columns in an alignment that allow to distinguish taxa and classifies them into four different types of diagnostic characters. Thus, cryptic taxa do not have to remain in taxonomic crypsis and, bearing a proper name, can be included in biodiversity assessments and ecological and evolutionary analyses.